Kinerja Kepala Madrasah di MTs Al Hikmah Kelurahan Talang Kelapa Kec. Alang-Alang Lebar Kota Palembang - Ibrahim Ibrahim (El-Idare, 2020)
This article examines the headmaster of a tsanawiyah madrasa. The madrasa head as a top manager must be good and have the competency according to the PP's mandate. 13 of 2007 concerning School / Madrasah Standards. This article is a qualitative naturalistic, key informant for madrasah principals, teaching staff and education. While informants supporting the deputy head of the madrasa, students. Interview, documentation, and observation data collection techniques, data analysis techniques namely data reduction, data presentation, verification / conclusion drawing, and data triangulation. The conclusion is the performance of the madrasa head has been going well, such as carrying out an effective learning process, continuous improvement, carrying out self-reflection towards character building, educator and educational staff development, fostering responsive, anticipatory, and high achievement expectations, transparent management of education, and develop instructional leadership. The supporting factors of the competency of madrasah headmasters, structural, communication, teaching staff, education staff, students, and internal environment are conducive. Inhibiting factors of madrasa budget constraints, limited facilities, infrastructure, and an unfavorable external environment.